Protocol for sand control screen design of production wells for clayey silt hydrate reservoirs: A case study. Issue 5 (25th January 2020) - Li, Yanlong; Ning, Fulong; Wu, Nengyou; Chen, Qiang; Nouri, Alireza; Hu, Gaowei; Sun, Jiaxin; Kuang, Zenggui; Meng, Qingguo
Abstract: The process of extracting natural gas from gas hydrate‐bearing sediments (GHBS) may yield significant sand influx due to the metastable nature of GHBS. Selecting appropriate sand control media is vital to addressing the challenges caused by excessive sand production. This study proposes a protocol called holding coarse expelling fine particles ( HCEFP ) for sand control design. The protocol aims to provide a new optimization method for screen mesh size selection for clayey silt hydrate reservoirs. Detailed optimizing procedures of proper candidate screen mesh sizes in hydrate exploitation well in clayey silt hydrate reservoirs are depicted based on the HCEFP . Then, the site W18, which is located in the Shenhu area of the northern South China Sea, is taken as an example to illustrate the optimization procedure for screen mesh size selection. The results reveal that complete solid retention via a standalone screen is rarely beneficial as high clay contents can adversely affect wellbore productivity due to excessive plugging. Screen aperture size selection for clayey silt hydrate wells should strike a balance between retaining coarser particles and avoiding screen blockage by the relatively fine particles. Furthermore, longitudinal heterogeneity of the PSDs also increases the difficulties associated with sand control design. Multistage sand control optimization is necessary in hydrate production wells. For Site W18, we recommend that the entire production interval can be divided into two subintervals for multistage sand control operations. Abstract : Excessive sanding challenges sand control in clayey silt hydrate production well. Hold‐coarse but expel‐fine method balances sand retention and screen plug requirement. Multistage sand control optimization recommended for clayey silt hydrate production well.